ANALISIS WACANA KRITIS PADA IKLAN LAYANAN PENDIDIKAN; KAJIAN NORMAN FAIRCLOUGH - Waiz Firdaus; Munirah; Andi Adam (Universitas Muria Kudus, 2026)
This study aims to analyze the discourse of educational service advertisements by examining how language is used to construct meaning, ideology, and power relations in the educational context. The phenomenon of the increasing use of advertisements as a medium for shaping the image of educational institutions is the main background of this study. The study uses a descriptive qualitative approach with Norman Fairclough's Critical Discourse Analysis framework. The research data consists of verbal texts of educational service advertisements collected through documentation techniques. The sample was determined purposively based on the criteria of relevance, message clarity, and dominant persuasive elements. Data analysis was conducted by examining three dimensions of discourse: text, discursive practices, and social practices. The results show that educational service advertisements utilize linguistic strategies such as metaphors, persuasive slogans, and imperative sentence structures to represent education as the main path to success and social mobility. These findings indicate that educational advertisements are not neutral, but rather reproduce certain ideologies and construct symbolic power relations between educational institutions and society. This study contributes to the development of critical discourse analysis studies in the fields of language and education and encourages increased public critical awareness of educational discourse in the media. Further research is recommended to involve multimodal analysis and audience reception studies.